Fraksinasi dan Identifikasi Ektrak Daun Mitragyna Speciosa Menggunakan Metode Kromatografi - Fernanda, M.A. Hanny Ferry; Suryandari, Mercyska; Sudarwati, Tri Puji Lestari (FARMASIS: Jurnal Sains Farmasi, 2021)
Background: Mitragyna Speciosa or better known as Kratom is a typical plant from the Putusibau area, West Kalimantan. The most widely used part of this plant is the leaves. The kratom plant contains alkaloids, flavonoids, phenols, terpenoids-steroids, triterpenoids, saponins, and tannins. Alkaloid content is the most dominant and has benefits in this plant so it is necessary to do fractionation and identification of secondary metabolites. Objective: To fractionate and identify secondary metabolites from Mitragyna Speciosa leaf extract. Methods: The fractionation method was carried out using Column Chromatography while for identification using Thin Layer Chromatography. Results: 80 fractions were obtained from the column chromatography results, while the results of identification using thin layer chromatography showed that only the 2nd and 3rd fractions were obtained. The second fraction has two spots with Rf values of 0.51 and 0.73 and in the third fraction there are three spots with Rf values of 0.21; 0.52, and 0.74. Conclusion: Fractionation and identification by chromatographic method can be used as initial screening for secondary metabolite content in Mitragyna Speciosa leaf extract.